Sosialisasi Penerapan Strategi Inovasi untuk Meningkatkan Produktivitas UMKM Serta Penjualan dalam Kesejahteraan SDM Desa Watesprojo - Mochamad Irfan; Yusuf Rachman Al Hakim; Ahfi Nova Ashriana; Elly Joenarni (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service article focuses on the main issues faced by food processing Micro, Small, and Medium Enterprises (MSMEs) in Watesprojo Village, Mojokerto, namely stagnant productivity and sales due to the lack of implementation of innovation strategies, which directly hinders the improvement of the welfare of local Human Resources (HR). The main objectives of this activity are to increase MSMEs' understanding of innovation models, increase HR productivity through process innovation, and encourage significant sales increases through the adoption of digital marketing innovations. The method used was Participatory Action Research (PAR) for six weeks, involving hands-on workshops, personalized coaching clinics, simple technology transfers such as semi-automatic vacuum packaging, and intensive mentoring for e-commerce account creation and visual branding. The results of the community service showed a high level of success, evidenced by an average increase in innovation understanding scores of 71% and an increase in production output per working hour of 18%. The most significant impact was seen in the marketing aspect, where MSMEs recorded an average increase in online sales of 35%, expanding market reach beyond Mojokerto. Sociologically, this program successfully triggered proactive behavioral changes and fostered a new social institution in the form of a Local Leader, the